THE RELATIONSHIP BETWEEN KNOWLEDGE AND EARLY WEANING OF BREASTFEEDING - Amellia Mardhika; Nopi Ispari Indah; Anestasia Pangestu Mei Tyas; Lailatul Fadliyah; Emuliana Sulpat (Journal of Vocational Nursing, 2025)
Introduction: Exclusive breastfeeding is recommended for the first six months of life and may be continued until the child is two years old, providing numerous benefits for the mother, baby, family, and nation. However, not all mothers breastfeed for the full six months, a practice known as early weaning. This study aims to analyze the relationship between mothers’ knowledge and early weaning practices. This study aims to analyze the relationship between knowledge and early weaning of breastfeeding. Methods: This quantitative analytical study was conducted in May 2024 at the Kebomas Community Health Center. A total of 44 mothers with children aged 6–24 months who met the inclusion criteria were selected using purposive sampling. Data on mothers’ knowledge regarding breastfeeding and early weaning were collected using a structured questionnaire and analyzed using the chi-square test with SPSS. Results: The findings indicate a relationship between mothers’ knowledge and early weaning practices in the Kebomas Community Health Center working area. Conclusions: Breastfeeding has positive effects on mothers, babies, families, and the nation. If early weaning is practiced by many mothers who lack knowledge about breastfeeding, these benefits may be lost. Education and counseling for pregnant women, continued through the postpartum period, are needed to prevent early weaning.